Thermodynamic investigation of the interaction between ionic liquid functionalized gold nanoparticles and human serum albumin for selective determination of glutamine. Issue 52 (26th August 2020) - Sahu, Sushama; Reshma,; Sharma, Srishti; Karbhal, Indrapal; Ghosh, Kallol K.
Abstract : The excellent biocompatible and monodispersed gold nanoparticles (AuNPs) functionalized by amino based ionic liquid (IL) have been synthesized for the demonstration of their interaction with human serum albumin (HSA). Abstract : The excellent biocompatible and monodispersed gold nanoparticles (AuNPs) functionalized by amino based ionic liquid (IL) have been synthesized for the demonstration of their interaction with human serum albumin (HSA). Amino based IL stabilizes the surface of AuNPs and provides a colorimetric sensor platform. The size of synthesized IL–AuNPs was identified by use of transmission electron microscopy (TEM) and dynamic light scattering (DLS) techniques. Molecular interaction of functionalized AuNPs with HSA have been investigated using multispectroscopic techniques, such as UV-Vis, fluorescence and Fourier transform infra-red (FT-IR) spectroscopy. The fluorescence and synchronous fluorescent intensity together indicated that IL–AuNPs exhibits a strong ability to quench the intrinsic fluorescence of HSA via a dynamic quenching mechanism. Moreover, the binding constant ( K a ), Stern–Volmer quenching constant ( K SV ) and different thermodynamic parameters, namely Gibb's free energy (Δ G ), enthalpy (Δ H ) and entropy (Δ S ) have been evaluated at different temperatures. This interactive study focuses on the nature of surface modification of IL–AuNPs via HSA for selective detection of glutamine (Glu) with a lower limit of detection of 0.67 nM in the linear range of 10–100 nM for Glu.